The economics of the financial crisis : lessons and new threats - Annunziata, Marco, 1965- (Houndmills, Basingstoke ; New York : Palgrave Macmillan, 2011)
Through the tools of economics, Annunziata's vivid and gripping book shows how the global financial crisis was caused by a failure of leadership and common sense in which we all played a role. The insights of this clear and compelling analysis are essential for learning the right lessons from the crisis, and seeing new threats around the corner.
Includes bibliographical references and index.
oif 08/09/14
Loan
Keywords: Financial crises; Business cycles; Globalization; Finance; Economic Conditions; Monetary Policy; Strategic Planning